Effects of some gelling agents and their concentrations on conversion of oil palm polyembryoids into plantlets - Palanyandy, Sharrmila Rengeswari; Gantait, Saikat; Sinniah, Uma Rani (SpringerOpen, 2020)
Oil palm, a tropical plant with an economic life of 20–25 years, is on high demand since its oil (palm oil) is now considered to be the world’s most consumed oil. Despite the high potential for the use of clonal materials, the tissue culture technique for oil palm is difficult and laborious. One of the key steps of the process is the conversion of polyembroids into plantlets. Gelling agent has been implicated to play a role in ensuring the conversion of oil palm polyembryoids into complete plantlets. In the present study, for the first time, we report the effects of two types of common gelling agents, Agar Type 900 and Gelrite®, for enhanced conversion of oil palm polyembryoids into plantlets. Polyembryoids, developed from embryonic calli, were cultured and incubated on Murashige and Skoog semisolid media supplemented with Agar (Type 900) at 8–12 g/l or gellan gum (Gelrite®) 1.5–3.5 g/l. The effects of gelling agents on polyembryoid conversion was assessed based on the percentages of viability, survival, and polyembryoids that swelled, enlarged, and turned green, as well as on the basis of morphological characteristics, viz, number of shoots, leaves, roots, secondary somatic embryos, and callus formation. Based on the results of this study, in comparison to Agar Type 900, the Gelrite® with 3.5 g/l concentration was chosen as an effective gelling agent for conversion of polyembryoids into plantlets, since it resulted in 100% survival with 53.3% completely developed plantlets (multiple shoots with roots). The successful conversion of polyembryoids into plantlets achieved in this study, using the optimized gelling agent could be useful for pre-storage or post-storage conversion in many other plant species as well.